Avaliação da qualidade de vida dos pacientes com psoríase: serviço de dermatologia UFPA/FSCM-PA, janeiro de 2002 a abril de 2007 - ANDRADE, Loana Marquez (2023)
Background: Psoriasis has a profound effect on the lives and well being of patients with the disease. Different studies have reported of social, physical and psychological disadvantages in patients with psoriasis Objectives: To evaluate the quality of life of the patients with diagnosis of psoriasis registered in the Service of Dermatology UFPA/ FSCM-PA, in the period of January of 2002 to the April of 2007. Patients and Methods: The patients had been selected from the book of register of the service. After that, an interview was set, in which, they answered the protocol standard of the study; the Psoriasis Disability Index (PDI) was applied, instrument that considers the evaluation of the quality of life . The extension of the illness was classified using as parameter the palm of the hand of the patient as being equivalent 1% of its corporal surface. Results: Thirty patients had appeared to the interview and had agreed to participate of the study. The majority of cases were females (66,7%) and the mean age was 51,1 years. Most respondents were diagnosed with chronic plaque psoriasis (93,3%). The mean value of PDI was 12, 1 which represents a percentage of global disability the 26,8%. Disability was greatest for the individual PDI area related to activities of daily living (36,7%). Patients with severe psoriasis (>10% of body surface area), present greater impact of quality of life than patients with moderate psoriasis (2%- 10% of body surface area) and these in turn present greater damage of that those with little involvement of psoriasis (p = 0,0338). The correlation between the PDI and young patients was statistically significant. Conclusion: Psoriasis causes a negative impact of the patient’s quality of life, having a correlation between gravity and a bigger damage of the quality of life. One worse perception of the quality of life in younger patients (between 21 and 40 years old) was also found. Possibly these patients are more affected by the stigma of the illness.